2020
DOI: 10.1097/md.0000000000023055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of aspirin and rivaroxaban for venous thromboembolism prophylaxis after total hip or knee arthroplasty

Abstract: Background: The purpose of this meta-analysis is to compare the efficacy and safety of aspirin and rivaroxaban in the prevention of venous thromboembolism (VTE) following either total knee arthroplasty or total hip arthroplasty. Methods: A comprehensive literature search of several electronic databases (PubMed, Embase, and Web of Science) was conducted to identify relevant studies. Outcomes of interest included VTE rate, deep vein thrombosis (DVT) rate, pulmonary emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…When comparing ASA and NOAC, the former had less risk of blood transfusion than rivaroxaban (RR = 0.94) 264 . A large trial (3,424 patients) did not find significant differences between ASA and rivaroxaban in clinically important bleeding (1.29% vs. 0.99%) or major bleeding (0.47% vs. 0.29%) 263 , and a recent meta-analysis 269 could not find any significant differences in any bleeding, major bleeding, minor bleeding, gastrointestinal tract bleeding or wound hematoma, between ASA or any other comparator.…”
Section: - Which Vte Prophylactic Agent Used In Patients Undergoing T...mentioning
confidence: 98%
See 2 more Smart Citations
“…When comparing ASA and NOAC, the former had less risk of blood transfusion than rivaroxaban (RR = 0.94) 264 . A large trial (3,424 patients) did not find significant differences between ASA and rivaroxaban in clinically important bleeding (1.29% vs. 0.99%) or major bleeding (0.47% vs. 0.29%) 263 , and a recent meta-analysis 269 could not find any significant differences in any bleeding, major bleeding, minor bleeding, gastrointestinal tract bleeding or wound hematoma, between ASA or any other comparator.…”
Section: - Which Vte Prophylactic Agent Used In Patients Undergoing T...mentioning
confidence: 98%
“…Three major studies of safety comparisons were identified in the literature: LMWH versus ASA 248 , non-vitamin-K oral anticoagulants (NOAC, including direct factor Xa inhibitors and other, such as rivaroxaban, dabigatran, apixaban, ximelagatran, etc.) versus LMWH 249-262 or ASA 263-265 , and NOAC of different groups comparing to each other 252,266 . Bleeding rates are not always reported, and bleeding risks may be used as the surrogate.…”
Section: - Which Vte Prophylactic Agent Used In Patients Undergoing T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research [21][22][23], the ratio of TKA to THA ranged from 1.3 to 1.5, the mean age ranged from 69.9 to 71.2 years, and the proportion of female sex ranged from 82.0 to 83.9 %. Le et al [24] completed a protocol for meta-analysis with 97,677 patients and showed that aspirin was as effective as rivaroxaban in preventing VTE after THA or TKA. However, in terms of DVT, aspirin showed an increased risk compared with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the direct-acting oral anticoagulants (DOACs, non-vitamin K-dependent oral anticoagulant) as direct thrombin inhibitor (dabigatran) and Factor Xa inhibitor (rivaroxaban, apixaban, edoxaban) would be the standard treatment for prevention of stroke and thromboembolism in nonvalvular atrial fibrillation patients or other primary diseases [ 1 2 ].…”
Section: Introductionmentioning
confidence: 99%